Demographic crises during the Maoist period: A case study of the Great Flood of 1975 and the forgotten famine - Roser Alvarez-Klee; Ramon Ramon Mu\~noz (European Historical Economics Society (EHES), 2024)
Demographic crises and famines were recurring phenomena in China before the mid-20th century, with the Great Leap Forward Famine of 1959-61 often regarded as the last and one of the most severe in Chinese History. This article delves into the repercussions of the Great Flood of 1975 in Henan province. We reassess the demographic implications of this hydrological catastrophe and employ a well-established methodology to identify demographic crises and occurrences of famine. Contrary to official perspectives, our findings indicate absolute mortality numbers and population losses in excess of officially accepted accounts and the emergence of localised famine episodes in the last years of Maoist China, suggesting that the last famine in China might have occurred in the mid-1970s. We argue that this demographic crisis was not solely the result of a high-magnitude natural disaster but also had other components: long-term economic policies that failed to achieve a solid and strong population's nutritional status in Henan before 1975, along with short-term political decisions made during the flood, likely exacerbated its impact. Moreover, this disaster cannot be viewed in isolation from Mao's hydraulic policies in the 1950s.
Keywords: I18; J11; N55; Q10; 330; Demographic crisis; famine; hydraulic catastrophe; nutritional conditions; China